Impacto da colaboração e competição na experiência de fluxo em ambiente educacional gamificado - Lemos Filho, Alexandre Marinho (2019)
The technology present in today’s world has impacted considerably the way people live their lives, including the educational context, which has competing students’ interest with technologies such as the internet or video games. In that sense, the academy has sought ways to make the educational process more attractive to students, and through the Flow Experience students could provide in-school tasks in an intrinsic way. Introduced by Csikszentmihalyi, Flow Theory defines a state of mind where the individual is focused on his task so deeply that he does not even notice the passing of time, causing na autotelic experience. This masters research aims to investigate the consequences of a gamified educational environment with elements of competition and collaboration in the students’ flow experience. For this, an experimento was carried out with 127 students distributed among four groups (Individual, In Group, Individual Competition and Group Competition) in computer-supported learning sessions. Subjects were evaluated for the flow experience after the task was performed. Results suggest that both competition and collaboration applied alone has no effect on the flow experience. However, when applied together, they had significant effects on the flow experience.